Summary Proceedings of the thirty-seventh annual meeting of the Board of Governors September 6-9,1982 - International Monetary Fund; The World Bank (Washington, D.C., 1982)
These Summary Proceedings include statements, or portions of statements, relating to the work of the Fund presented by Governors during the meetings, resolutions adopted by the Board of Governors of the Fund over the past year, reports, recommendations and other documents relating to the Meetings.
usc 02/09/2021
Ref.
Keywords: International Monetary Fund; Foreign Exchange